Estudio de disipación de energía cinética en chorros para pequeñas estructuras hidráulicas (2020)
The study of the dissipation of kinetic energy in immersion jets has not had much development. Expanding research in this field allows to design collection chambers more efficiently in small hydraulic structures, making hydraulic designs more durable and functional. Recently research of dissipation bowls has been led by José María Carrillo (2014) and Luis Castillo (1989), mainly oriented to rectangular spillways. To expand knowledge in this field and contribute to the correct design of collection chambers, immersion and dissipation in low-flow hole jets are investigated. For the development of the work, an assembly was developed that allows the flow of jets with holes of 0.5, 0.75, 1 and 1.25 Inches. The assembly was worked with jets discharging flow between 0.11 l/s and 0.97 l/s that were impacted on a reservoir in which different volumes of wáter were stored, which we will henceforth call water mattresses, with 32 different heights ranging from 0mm to 300mm. For pressure measurement, 6 transducers were used where one corresponded to the impact point, and the others were separated 2.5cm and 5cm both upstream and downstream of the impact point. The combinations of holes, flow rates and water sheet heights in mattresses are the scenarios of this study. With the results obtained for the different scenarios, the graphical and numerical analysis of the incidence of each draft of the water mattresses in the dissipation of the kinetic energy of each of the jets is performed, both at the point of stagnation and at the surrounding points evaluated. A theoretical analysis is also carried out based on previous research carried out, especially in research developed for circular jets by Ervine (1997). Among the conclusions obtained are the water levels and key hydraulic ratios in which energy dissipation occurs, it is highlighted that the dynamic pressure has to dissipate in a water sheet heights - impact jet-diameter ratio (/) equal to 4, reaching total dissipation in a relationship /=20. It also highlights the relationship of the characterization of the jets and their immersion with the pressure results obtained. The work also makes recommendations for future research.